PENGARUH PERSEPSI KEMUDAHAN TERHADAP MINAT ULANG MENGGUNAKAN BRILINK MELALUI KEPUASAN PELANGGAN DI DESA SENDEN KECAMATAN KAMPAK KABUPATEN TRENGGALEK - Suniya Sova Ayu Lestari; Rifki Hanif (UNIVERSITAS PGRI MADIUN, 2023)
One of the well-known banks in the community is BRI, which has BRILink Agent services and has spread to many regions of Indonesia. The importance of convenience can affect a person's satisfaction and also interest in reusing a banking transaction service. This study aims to examine the effect of customer satisfaction as a mediation between perceived convenience and interest in reusing BRILink services in Senden Village, Kampak District, Trenggalek Regency. This study uses a quantitative research approach with path analysis. The type of research used is causal research with observation method. Data obtained by distributing questionnaires to respondents obtained 100 samples through accidental sampling technique. Based on the results of the study it is known that indirectly perceived convenience influences repurchase intention through customer satisfaction. Meanwhile, perceived convenience does not directly affect repurchase intention